Legal Aspects Of Consumer Protection In Illegal Sale Of Telecomunication Devices In Indonesia - Erry Fitrya Primadhany; Imam Wahyudi; Cahyati Cahyati (Magister Ilmu Hukum Fakultas Hukum Universitas Syiah Kuala, 2020)
Regulations regarding transaction of telecommunication devices have been clearly regulated. However, the circulation of illegal products is still rife, especially devices that International Mobile Equipment Identity (IMEI) is not officially registered. This can potentially be detrimental to consumers. This research is normative research with the legal research method of literature. The approach used is a statutory approach and a conceptual approach. It can be concluded that the protection that can be done against consumers is preventive protection that is preventive and repressive protection that is done if the consumer has suffered a loss. Preventive preventive legal protection is contained in the provisions of Law No. 8 of 1999 on Consumer Protection and also contained in government efforts through Regulation of the Minister of Communication and Informatics No. 1 of 2020.Repressive legal protection can be resolved through litigation and non-litigation litigation.Violation of product requirements rules may result in businesses being subject to administrative sanctions.